"Cultural distance" among speakers of the same language - Gómez Parra, Elena (Sens public)

(untitled) (Département des littératures de langue française, 2009)
According to Byram (1997), intercultural competence means to be able to interact efficiently with persons from various countries in a foreign language. The paper introduces a new concept, in a sensible disaccord with this definition, the concept od « cultural distance » that exists between persons speaking the same language but do not share the same cultural values. We will introduce examples to illustrate some cases of a large cultural distance between speakers of the same language (in this case, Spanish).